Penyuluhan tentang Imunisasi Dasar, Vitamin A dan Tumbuh Kembang pada Bayi dan Balita di Wilayah Puskesmas Jenggot Kota Pekalongan - Putri Andanawarih; Miftachul Jannah (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2020)
Supporting and maintaining surveillance of immunization programs and provision of Vitamin A in Indonesia is one of the efforts in reducing MMR and IMR. Immunization is one of the most effective public health interventions in preventing morbidity and mortality. Vitamin A is one of the important nutrients that is fat soluble and stored in the liver, cannot be produced by the body, so it must be fulfilled from the outside (essential), functioning to vision, growth and increase the body's resistance to disease. Vitamin A is useful for reducing mortality and morbidity, because of that vitamin A can increase the body's resistance to infectious diseases such as measles, diarrhea, and Acute Respiration Infection (ISPA). Other consequences that have a very serious impact from Vitamin A Deficiency (KVA) are night blindness and other manifestations of xeropthalmia including corneal damage and blindness. The team conducted community service under the title "Counseling about Basic Immunization, Vitamin A and Growth in Infants and Toddlers in the Jenggot Public Health Center-Pekalongan ". The methods of counseling basic immunization programs for infants and toddlers, providing vitamin A and monitoring the growth and development of children. The results of the evaluation of activities on the post test results were 35% on knowledge about immunization and 48% on knowledge of vitamin A.